XIII Conference "Root and Butt Rot of Forest Trees" IUFRO Working Party 7.02.01 September 4th-10th 2011 Firenze - Auditorium di S. Apollonia S. Martino di Castrozza (TN) - Palazzo Sass Maor, Italy - Garbelotto, Matteo; CAPRETTI, PAOLO; Comparini, Cecilia; La Porta, Nicola (Proceedings e report, 2013)
The present Proceedings comprise the contributions that were presented at the 13th International Conference of the IUFRO W. Party 7.02.01 "Root and Butt Rot of Forest Trees" that was held in Italy from the 4th to the 10th of September 2011. The Conference started in Firenze than moved to FEM Research Centre, S. Michele all'Adige, Trento and continued in San Martino di Castrozza, Dolomite region. Root and Butt Rot of Forest Trees have a high biological and economic impact in forestry. The Proceedings were organized under seven headings: Genomics and Plant-Pathogen Interactions; Systematics, Taxonomy and Phylogeography; Ecology; Population Genetics; Etiology and Epidemiology; Disease Management and Control; New Reports, Diagnostics and Research on the Application of new Diagnostic Methods.